John F. Kennedy on leadership : the lessons and legacy of a president - Barnes, John A., 1960- (AMACOM, American Management Association, 2005)
Whether in business, politics, or the community, today's leaders have more in common with their legendary predecessors than they may realize. Intensely scrutinized by their constituents, colleagues, the media, and the public, leaders make decisions that affect lives far beyond their immediate surroundings.
Includes index.
Keywords: Kennedy, John F. -- (John Fitzgerald), -- 1917-1963.; Kennedy, John F. -- (John Fitzgerald), -- 1917-1963; Leadership -- Case studies.; Communication in management -- Case studies.; Teams in the workplace -- Case studies.; Decision making -- Case studies.; Crisis management -- Case studies.; elektronické knihy; electronic books